Repurposing dimethyl fumarate for cancer therapy: current evidence and future directions - Zhang, Mingjuan; Jing, Yaping; Cui, Qingbin (Frontiers in Pharmacology, 2025)
Dimethyl fumarate (DMF) is an approved medication by the FDA for the treatment of multiple sclerosis, primarily targeting and regulating the NF-κB pathway. Recently, its anticancer effects have drawn considerable attention as it not only effectively kills a panel of different cancer cells in vitro and in vivo, but also synergizes with other conventional or targeted chemotherapeutics in certain resistant or refractory cancer cells. Mechanism studies showed that in addition to inhibiting NF-κB and stimulating Nrf2, DMF functioned as a chemotherapy also by suppressing inflammation, inhibiting epigenetic modifications, as well as modulating epithelial-mesenchymal transition (EMT). On the molecular level, DMF can form a covalent bond with the thiol group of a protein. In this paper, we provide a brief review of the anticancer studies of DMF, either as a single agent or in combination regimens. While DMF is a relatively weak cytotoxic agent, it is effective in sensitizing cells to other chemotherapeutic agents. Since DMF is already an approved drug, its fast-track approval for cancers may bring new hope to those chemo-resistant patients who suffer from very limited treatment options.